Multiple delivery strategies of nanocarriers for myocardial ischemia-reperfusion injury: current strategies and future prospective - Shengnan Li; Fengmei Li; Yan Wang; Wenqun Li; Junyong Wu; Xiongbin Hu; Tiantian Tang; Xinyi Liu (Drug Delivery)
Acute myocardial infarction, characterized by high morbidity and mortality, has now become a serious health hazard for human beings. Conventional surgical interventions to restore blood flow can rapidly relieve acute myocardial ischemia, but the ensuing myocardial ischemia-reperfusion injury (MI/RI) and subsequent heart failure have become medical challenges that researchers have been trying to overcome. The pathogenesis of MI/RI involves several mechanisms, including overproduction of reactive oxygen species, abnormal mitochondrial function, calcium overload, and other factors that induce cell death and inflammatory responses. These mechanisms have led to the exploration of antioxidant and inflammation-modulating therapies, as well as the development of myocardial protective factors and stem cell therapies. However, the short half-life, low bioavailability, and lack of targeting of these drugs that modulate these pathological mechanisms, combined with liver and spleen sequestration and continuous washout of blood flow from myocardial sites, severely compromise the expected efficacy of clinical drugs. To address these issues, employing conventional nanocarriers and integrating them with contemporary biomimetic nanocarriers, which rely on passive targeting and active targeting through precise modifications, can effectively prolong the duration of therapeutic agents within the body, enhance their bioavailability, and augment their retention at the injured myocardium. Consequently, these approaches significantly enhance therapeutic effectiveness while minimizing toxic side effects. This article reviews current drug delivery systems used for MI/RI, aiming to offer a fresh perspective on treating this disease.